SKB 3 MENTERI DAN IMPLIKASINYA PADA PENDIDIKAN ISLAM - Salman Alfarisi; Yunus Abu Bakar (IAIN Sorong, 2022)
Madrasas as one of the Islamic educational institutions in Indonesia have a long history in this nation. Formally, madrasas were developed in response to two important conditions, namely Islamic reform in Indonesia and education under Dutch supervision. In its journey, Madrasah experienced many twists and turns, starting with the disallowance of it during the Dutch era, being recognized and allowed to operate during the Old Order, and not being recognized during the New Order. This article will try to explore the implications of conditions in the New Order era until the issuance of three ministerial decrees which reduced the dualism of education issues and improved the quality of madrasas. The issuance of the decree was a springboard for integrating madrasas into the national education system